2005
DOI: 10.1081/clt-200058936
|View full text |Cite
|
Sign up to set email alerts
|

Methanol and Formate Kinetics During Treatment with Fomepizole

Abstract: Based on our data, methanol-poisoned patients with moderate metabolic acidosis and methanol levels up to 19 mmol/L (60 mg/L) may safely be treated with bicarbonate and fomepizole only, without dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 0 publications
1
33
1
1
Order By: Relevance
“…The variability of the endogenous elimination of formate may in part be explained by its variable renal excretion as also reported in the same patients 27 and in patients not undergoing dialysis. 27 We have previously suggested that this variation in the renal handling of formate is pHdependant; the more acidic the urine becomes, the less formate is excreted: Therefore, the role of dialysis in removing formate most probably becomes more important the more acidotic the patient is because the intrinsic clearance of formate then decreases. 27 We have recently published a fatal case report of a 63-year-old male presenting with a severe metabolic acidosis following methanol poisoning.…”
Section: Comments/discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The variability of the endogenous elimination of formate may in part be explained by its variable renal excretion as also reported in the same patients 27 and in patients not undergoing dialysis. 27 We have previously suggested that this variation in the renal handling of formate is pHdependant; the more acidic the urine becomes, the less formate is excreted: Therefore, the role of dialysis in removing formate most probably becomes more important the more acidotic the patient is because the intrinsic clearance of formate then decreases. 27 We have recently published a fatal case report of a 63-year-old male presenting with a severe metabolic acidosis following methanol poisoning.…”
Section: Comments/discussionmentioning
confidence: 74%
“…27 Again, the benefit may seem marginal, but this is a complex issue: first, the patients where formate kinetics was performed during dialysis were more severely poisoned. That means they were more acidotic on admission, and hence the endogenous formate half-life in these patients would most probably be significantly longer without dialysis.…”
Section: Hemodialysis and Methanolmentioning
confidence: 98%
See 1 more Smart Citation
“…Methanol is primarily cleared by metabolism, so its half‐life during fomepizole therapy is increased (50–80 h) . Haemodialysis is often used to shorten the duration of therapy and hospital stay , and intermittent haemodialysis has been shown to be superior to continuous dialysis modalities .…”
Section: Treatment With Fomepizolementioning
confidence: 99%
“…In the UK the competitive alcohol dehydrogenase antagonist fomepizole is available for use in ethylene glycol poisoning [186] and methanol poisoning on a named patient basis [187]. This agent may still be required in conjunction with extracorporeal removal as methanol redistribution postdialysis may occur [188, 189].…”
Section: Normal Anion Gap Acidosesmentioning
confidence: 99%